An aged life has less value: A qualitative analysis of moral disengagement and care failures evident in Royal Commission oral testimony. Issue 23 (24th May 2021) - Austen, Katrina; Hutchinson, Marie
Abstract: Aims and objectives: To identify common themes about care failures in residential aged care as described from the perspectives of older people and their families in transcripts from hearings and submission to the Australian Royal Commission. These failures are explored through the lens of moral disengagement. Background: Previous inquiries into care failures have highlighted widespread harm from inhumane care, caused by staff carelessness, indifference and callousness. In health care, limited consideration has been given to the moral engagement or disengagement of staff and the relationship of moral engagement with care failures. Method: Qualitative latent content analysis of 22 transcripts from the Royal Commission between March 2020–August 2020. Methods are reported using the SRQR. Results: This paper presents one theme, Dehumanisation of the care process : An aged life has less value, from a larger study. Care failures relating to morally disengaged staff were found to be widespread and influenced by the environments created by organisations. Conclusion: This study highlights the need for further research to identify indicators of moral disengagement among staff and explore strategies to reduce or prevent moral disengagement within organisations trusted with providing care to older people. Relevance to clinical practice: Caregiving is necessarily associated with, and shaped by, moral dimensions. The erosion or disengagement of these moral dimensions among care staff reveals important aspects of residential aged care's lived experience. Studying dynamics within aged care facilities can provide a useful analytic lens for illuminating ways that residents and their family or those close to them, experience or are impacted by moral dimensions and behaviours.